LANDASAN FILSAFAT ( HUKUM DAN MORAL ) KEWARGANEGARAAN REPUBLIK INDONESIA - Suryono, Hassan (PKn Progresif, 2008)
The aim of this writing the search for truth is the basis philosophy, philosophy of law and moral philosophy from the citizenship of the Republic of Indonesia. The result is that the foundation of philosophy from the citizenship of the Republic of Indonesia is protect all the Indonesian people and the entire homeland of Indonesia and to promote the general welfare clause 26 and the 1945 Constitution regarding the establishment of a citizen and resident. Philosophy of law from the foundation of citizenship of the Republic of Indonesia in a moral democracy led by wisdom of the policy / legal representative and primary / remembrance / of Law No 12 year 2006. Platform is the moral values of the Pancasila.